Partnering for Progress: Lessons Learned From Mental Health Assessment for Youth Living With HIV in India Through Community-Based Participatory Research - Siddhaparna Sannigrahi; Babu Seenappa; Prashant Lakshmikanth; Suhas Reddy; Kacie Filian; Michael Babu Raj; Lakshmi Ganapathi; Anita Shet (Journal of Participatory Research Methods)
Youth living with HIV (YLHIV) face diverse mental health challenges necessitating interventions informed by their lived experiences. Failure to do so can perpetuate a self-reinforcing cycle of misaligned and ineffective support, further exacerbating existing vulnerabilities. This study directly addresses this gap by using a community-based participatory research (CBPR) approach to empower YLHIV in India to address their mental health challenges. YLHIV actively participated in adapting and implementing a culturally responsive mental health screening program. The study, incorporating CBPR principles at every step aimed to identify practical methods for integrating YLHIV voices in research, and showcase the value of YLHIV participation in co-creating and implementing impactful interventions. Six youth investigators aged 18-24, born with HIV and residing in southern Indian states underwent certification in human subjects' protection and training in mental health screening and survey administration techniques. They actively shaped the research process by culturally adapting standardized mental health screening tools (PHQ-9, GAD-7) through iterative discussions with experts, drawing on their own perspectives. Following field assessments of the mental health screening tools among their peers, they documented their reflections in surveys and written essays. Youth investigators’ involvement improved the research process by optimizing tools, combating stigma, and facilitating reliable data collection. Beyond data collection, the youth investigators’ participation significantly boosted their own knowledge, self-confidence, and research skills. This study serves as an illustrative model of CBPR in mental health research among YLHIV, highlighting the importance of interactive training, continuous feedback mechanisms, and respectful youth engagement in fostering impactful research that can inform tailored sustainable interventions.